1983
DOI: 10.1097/00000658-198305000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Management of the Major Coagulopathy with Onset during Laparotomy

Abstract: An experience with 31 patients who developed major bleeding diatheses during laparotomy was reviewed. Management of the initial 14 patients was by standard hematologic replacement, completion of all facets of operation, and then closure of the peritoneal cavity, usually with suction drainage; only one patient survived. The subsequent 17 patients had laparotomy terminated as rapidly as possible to avoid additional bleeding. Major vessel injuries were repaired; ends of resected bowel were ligated; and holes in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
288
0
28

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 591 publications
(316 citation statements)
references
References 3 publications
0
288
0
28
Order By: Relevance
“…1,[4][5][6][7]9 Although the technique of perihepatic packing was founded in 1908 with Pringle's discussion of hepatic trauma, 43 the modern interpretation of this work occurred in the late 1970s, [44][45][46] followed by the concept of truncated operations with concurrent intra-abdominal packing for patients in physiologic extremis by Stone and colleagues in 1983. 47 This philosophy was then coined "damage control" by Rotondo and colleagues, given its obvious conceptual similarity to the Navy's use of the same term. 48,49 Although this concept has resulted in a substantial improvement in mortality when applied to the correct patient population, 49 it also commits the patient to a series of subsequent operative procedures aimed at restoring gastrointestinal continuity and abdominal wall closure.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6][7]9 Although the technique of perihepatic packing was founded in 1908 with Pringle's discussion of hepatic trauma, 43 the modern interpretation of this work occurred in the late 1970s, [44][45][46] followed by the concept of truncated operations with concurrent intra-abdominal packing for patients in physiologic extremis by Stone and colleagues in 1983. 47 This philosophy was then coined "damage control" by Rotondo and colleagues, given its obvious conceptual similarity to the Navy's use of the same term. 48,49 Although this concept has resulted in a substantial improvement in mortality when applied to the correct patient population, 49 it also commits the patient to a series of subsequent operative procedures aimed at restoring gastrointestinal continuity and abdominal wall closure.…”
Section: Discussionmentioning
confidence: 99%
“…The true reawakening occurred in 1983 when Stone and his co-workers published a series of 17 severely injured patients treated with abbreviated laparotomy and planned reoperation with a survival rate of 76% when compared with 14 similar patients undergoing definitive repair with only one survivor (7%) (6). The concept was further refined by Ivatury in 1986 (7) and Burch in 1992 (8).…”
Section: History Of Damage Control Surgerymentioning
confidence: 99%
“…Jurkovich et al (7) found that no trauma patient whose core temperature fell below 32 °C survived, and they regarded this as the critical temperature for survival. Hypothermia is recognized as one pillar of a -lethal triad‖ (hypothermia, acidosis and coagulopathy) of homeostatic failure that is believed to mark the limits of ongoing intervention, and necessitates an -abbreviated‖ laparotomy (26)(27)(28)(29)(30) .…”
mentioning
confidence: 99%